A grounded theory research on fintech startups in the Philippines - Danao, Matthew Emmanuel D. (Animo Repository, 2023)
The Philippines has promoted startups for Economic Development in recent years. Startups, particularly FinTech startups, have seen an increase in number over the past few years which is likely attributable to the COVID-19 pandemic producing an influx of digital adopters, growing the country’s FinTech user base. With the country posing a 27 to 30 percent growth rate in digital payments, the future of the local FinTech industry is bright. Despite the growing industry, it remains understudied with multiple studies arguing that the foundations for knowledge of startup research are yet to be analyzed. This paper then intends to gain a better understanding of the key factors that contribute to the decision-making process of FinTech startups in the Philippines. This study used a qualitative, Grounded Theory approach to gain a deeper understanding of the experiences and perspectives of the individuals involved in the creation of these startups. Six (6) participants, who were a mix of startup founders and key team members during the startup's infancy stages, were interviewed using semi-structured interviews with open-ended questions. These were then coded and generated six (6) common themes, namely the (1) Business Model, (2) Founder, (3) Market, (4) Problem, (5) Product, and (6) Testing. Further analysis suggests that FinTech startups prioritize organizational goals over profit-maximization. With that, a profit satisficing model is used to represent the relationship of FinTech startups and their goals relative to profit.